Erratum to “Anti-Inflammatory Effect of 3-Bromo-4,5-Dihydroxybenzaldehyde, a Component of Polysiphonia morrowii, In Vivo and In Vitro” [Toxicol. Res. 33 (2017) 325-332] - Kang, Na-Jin; Han, Sang-Chul; Kang, Hyun-Jae; Ko, Geum; Yoon, Weon-Jong; Kang, Hee-Kyoung; Yoo, Eun-Sook (Toxicological research (Seoul), 2018)
On page 327 and 328, the authors found labeling errors in Fig. 2B and Fig. 3B. Fig. 2B is originally result for “IgE levels” but was erroneously expressed as “ear thickness”. Therefore author wanted to change from Fig. 2B ear thickness results to IgE levels and from Fig. 3B to corrected “ear thickness” results.